2012
DOI: 10.1155/2012/812192
|View full text |Cite
|
Sign up to set email alerts
|

Some Clarifications Regarding Literature on Atmospheric Corrosion of Weathering Steels

Abstract: Extensive research work has thrown light on the requisites for a protective rust layer to form on weathering steels (WSs) in the atmosphere, one of the most important is the existence of wet/dry cycling. However, the abundant literature on WS behaviour in different atmospheres can sometimes be confusing and lacks clear criteria regarding certain aspects that are addressed in the present paper. What corrosion models best fit the obtained data? How long does it take for the rust layer to stabilize? What is the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 16 publications
2
21
0
2
Order By: Relevance
“…The most steady-state start times are less than 6th year. Meanwhile, the trend of stabilization time is not very consistent with [4]. But the trend of average corrosion rate when exposure time reached the stabilization corresponded to the common sense.…”
Section: Results and Analysismentioning
confidence: 81%
See 1 more Smart Citation
“…The most steady-state start times are less than 6th year. Meanwhile, the trend of stabilization time is not very consistent with [4]. But the trend of average corrosion rate when exposure time reached the stabilization corresponded to the common sense.…”
Section: Results and Analysismentioning
confidence: 81%
“…Another literature [4] proposed that rural and urban atmospheres have the similar stabilization time (3-5 years). And the value for industrial atmospheres is longer than rural and urban atmospheres (5-10 years).…”
Section: Introductionmentioning
confidence: 99%
“…Small amounts of alloying elements such as Cu and Cr contribute to maintain a nano-amorphous protective layer on the metal surface, thus preventing diffusion of corrosive species to the metal surface. Weathering steel has performed well in industrial environments where there is high SO 2 [8] and CORTEN A has been found to yield sufficient corrosion resistance in the gas preheater in oil-fired power plants where there is high sulphur content [9]. It is reported that copper in weathering steels forms copper hydroxy sulphates in SO 2 environments, and these compounds precipitate in pores of the rust layer and thus hinder ingress of corrosive species [8].…”
Section: Corrosion Of Weathering Steel Rotor and Its Consequencesmentioning
confidence: 99%
“…Weathering steel has performed well in industrial environments where there is high SO 2 [8] and CORTEN A has been found to yield sufficient corrosion resistance in the gas preheater in oil-fired power plants where there is high sulphur content [9]. It is reported that copper in weathering steels forms copper hydroxy sulphates in SO 2 environments, and these compounds precipitate in pores of the rust layer and thus hinder ingress of corrosive species [8]. When the required wet/dry cycles are not present, high corrosion rates were measured, and maghemitite γ-Fe 2 O 3 or akaganeite β-FeOOHCl forms if Cl is present [10].…”
Section: Corrosion Of Weathering Steel Rotor and Its Consequencesmentioning
confidence: 99%
“…Existen varias explicaciones entre los investigadores sobre el positivo efecto del Níquel en la protección a la corrosión en ambiente marino. Los investigadores han demostrado el desplazamiento del potencial de corrosión a valores positivos estabilizando el acero, así como también la formación de especies iónicas selectivas que repelen el avance de los iones cloruro [5,6]. Estos estudios se llevan a cabo en condiciones atmosféricas, los que pueden llevar años en completarse.…”
Section: Introductionunclassified